1995
DOI: 10.1103/physrevlett.74.4129
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetric Minisuperspace with Nonvanishing Fermion Number

Abstract: The Lagrangian of W = 1 supergravity is dimensionally reduced to one (timelike) dimension assuming spatial homogeneity of any Bianchi type within class A of the classification of Ellis and McCallum. The algebra of the supersymmetry generators, the Lorentz generators, the diffeomorphism generators, and the Hamiltonian generator is determined and found to close. In contrast to earlier work, infinitely many physical states with nonvanishing even fermion number are found to exist in these models, indicating that m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
93
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 29 publications
4
93
1
Order By: Relevance
“…Due to the different ordering chosen, the algebra (6)-(9) differs slightly from a corresponding result given in [11], but both forms are, of course, fully consistent.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…Due to the different ordering chosen, the algebra (6)-(9) differs slightly from a corresponding result given in [11], but both forms are, of course, fully consistent.…”
mentioning
confidence: 84%
“…Subsequently it was shown [10] that the particular SO(3) symmetry of Bianchi type IX permits an alternative homogeneity ansatz for the Rarita-Schwinger field, and that its application replaces the permitted 'worm-hole' state in the empty or filled fermion sector by a 'no-boundary' state in the same sector. In a recent paper [11] we reexamined the supersymmetric minisuperspace models of Bianchi type in class A [12] without matter fields and showed that, contrary to previous expectations, they posses infinitely many physical states. Hence, the question of the existence and form of a 'no-boundary' state in such models must be reconsidered.…”
mentioning
confidence: 99%
See 3 more Smart Citations